ANSWERING TO THE CALLS OF DIGITIZATION: THE CRUCIAL ROLE OF ENTREPRENEURIAL AGILITY - Tuti Asmala; Ahmad Johan; M Dana Prihadi (Faculty of Business, President University, 2022)
Introduction/Main Objectives: The purpose of this study is to examine the mediating role of entrepreneurial agility in the relationship between digital platform capability and business model innovation adoption, while also considering the moderating role of technology opportunism and environmental dynamism. Background Problems: Digitization currently influences every aspect of individual, including the way they carry out business. Therefore, it is important to understand the way firms respond to this condition while conducting their business. Novelty: This study addresses how the business model innovation adoption can be more advanced and supported by digital platform capability by considering various conditions to deal with changes in technology and the environment, including entrepreneurial agility, environmental dynamism, and technology opportunism. Research Methods: This study is carried out using quantitative approach by distributing questionnaire to the owners or managers of creative MSMEs in Bandung, West Java. The respondents are chosen using purposive sampling method, with the number of samples of 120 respondents. The data is then analyzed with Structural Equation Modeling with AMOS 3.0. Finding/Results: Digital platform capability has a positive influence on entrepreneurial agility, which has a positive influence on business model innovation adoption. Entrepreneurial agility mediates the relationship between digital platform capability on business model innovation adoption, and this relationship is moderated by technology opportunism and environmental dynamism. Conclusion: This study highlights the importance of digital platform capability for firms, as it can lead them to have entrepreneurial agility, and ultimately carry out business model innovation adoption.